EDUKASI MANAJEMEN KEUANGAN RUMAH TANGGA UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Wahyuni, Siti; Hapsari , Fadjriah; Herawati, Mirna (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to improve community understanding and skills in managing household finances to support family welfare. The main issues include low financial literacy, lack of structured budgeting, and minimal expense-recording habits. The program applied a participatory educational approach consisting of preparation, training, evaluation, and mentoring stages. Activities included interactive lectures, discussions, and hands-on budgeting practice. Evaluation through pre-tests and post-tests showed increased participant understanding of financial planning, saving habits, and expenditure control. Follow-up mentoring supported the sustainable application of financial management practices. The results demonstrate that household financial education effectively enhances family economic independence and contributes to community welfare.